2014
DOI: 10.1002/asia.201400034
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed 6‐ExoDig Cycloisomerization: A Versatile Approach to Functionalized Phenanthrenes

Abstract: A novel gold-catalyzed 6-exo-dig cycloisomerization of o-propargylbiaryls has been developed that provides ready access to functionalized phenanthrenes in largely good to excellent yields. Notable features of this method are readily available starting materials, mild reaction conditions, and broad substrate scope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 89 publications
1
14
0
Order By: Relevance
“… 366 In a mechanistically related transformation, the synthesis of functionalized phenanthrenes 416 has been described from o -propargylbiaryls (Scheme 134 ). 367 Dibenzocycloheptatrienes were obtained by a related transformation through a 7- exo -dig hydroarylation. 368 …”
Section: Hydroarylation and Hydroheteroarylation Of Alkynesmentioning
confidence: 99%
“… 366 In a mechanistically related transformation, the synthesis of functionalized phenanthrenes 416 has been described from o -propargylbiaryls (Scheme 134 ). 367 Dibenzocycloheptatrienes were obtained by a related transformation through a 7- exo -dig hydroarylation. 368 …”
Section: Hydroarylation and Hydroheteroarylation Of Alkynesmentioning
confidence: 99%
“…In this case, the cyclization is favored at the less-hindered position of the aryl ring. [168] DFT studies initiated on model system in a separate study revealed that the competitive 7-endo-dig cycloisomerization is unlikely, because of the high activation energy of the rate determining step, making it unlikely to occur under ambient conditions. [169] By extending Fürstner's protocol, Davis et al was able to cyclize 2,6-bis-iodoalkynyl-biphenyl 132 through AuCl catalyzed 1,2-iodo shift/hydroarylation to prepare polysubstituted pyrene 133, albeit in low yield (Scheme 21, Eq.…”
Section: Site-selective Cà H Bond Functionalization Reactionsmentioning
confidence: 99%
“…The choice of the proper Ag salt is crucial, as when we performed the reaction under the same conditions but using AgOTf we observed a drop in the yield (entry 6). On the basis of these results, we aimed at increasing the electrophilicity of the gold complex and we synthesized (C 6 F 5 ) 3 PAuCl, a complex which has been reported to perform well in the hydroarylation of o ‐propargyl biaryls . The use of this strongly electron‐poor ligand in combination with AgNTf 2 led to an increase in the yield of 9a (entry 7), while AgOTf revealed again to be less suitable (entry 8).…”
Section: Resultsmentioning
confidence: 99%
“…Ye and colleagues reported the gold‐catalysed 6‐ exo ‐ dig cyclization of o ‐alkynyldiarylmethanes followed by isomerization of the double bond and aromatization to anthracenes. [2b] Phenanthrenes were synthesized by the same authors starting from propargyl biphenyls . More recently, Verma reported the synthesis of phenanthrenes by Ag(I) catalysis .…”
Section: Introductionmentioning
confidence: 99%